Faktor-Faktor Yang Mempengaruhi Inklusi Keuangan (Studi Pada Mahasiswa Magister Manajemen Universitas Sultan Ageng Tirtayasa) - Fitriah, Fitriah; Ichwanudin, Wawan (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2020)
This study aims to examine and analyze the effect of organizational commitment and level of discipline on employee performance through job satisfaction as an intervening variable. The implementation of this research is expected to provide theoretical benefits for academics and practitioners for the Department of Trade, Industry, Cooperatives and Micro, Small and Medium Enterprises, Serang City. The research method uses quantitative methods by using causality, namely looking for explanations in the form of causal relationships between several concepts or variables, the researcher collects primary data using a census questionnaire technique for 75 respondents and data analysis techniques with Partial Least Square (PLS) software. The results showed that organizational commitment and level of discipline had a direct effect on performance and there was an effect after being tested with the intervening variable job satisfaction.